Berlin Heinrichplatz: The Novels of Ulrich Peltzer - Christian Jäger (Studies in 20th & 21st Century Literature, 2004)
For at least a decade Germans have been waiting—waiting for literature, waiting for the great Berlin novel, waiting for the great novel of reunification…
Keywords: Ulrich Peltzer; Berlin; Berlin novel; reunification; novel; Heinrichplatz; Germany; German; Germans